Persistent monetary non-neutrality in an estimated menu-cost model with partially costly information - Marco Antonio Bonomo; Carlos Viana de Carvalho; René Garcia; Vivian Malta; Rodolfo Rigato (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2021)
We propose a model that reconciles microeconomic evidence of frequent and large price changes with sizable monetary non-neutrality. Firms incur separate lump-sum costs to change prices and to gather and process some information about marginal costs. Additional relevant information is continuously available, and can be factored into pricing decisions at no cost. We estimate the model by Simulated Method of Moments, using price-setting statistics for the U.S. economy. The model with free idiosyncratic and costly aggregate information fits well both targeted and untargeted microeconomic moments and generates almost three times as much monetary non-neutrality as the Calvo model.
Keywords: E00; E31; 330; menu costs; information costs; infrequent information; partial information; inattention; optimal price setting; state-dependent pricing; time-dependent pricing